Enfermedades por superantígenos en Dermatología Pediátrica: una serie de casos - Schroder Huaquín, Claudia; Aranibar Durán, Ligia (Revista Hospital Clínico Universidad de Chile, 2023)
Superantigen diseases (SAg) are part of a series of pathologies triggered or exacerbated by antigens, such as bacteria or viruses, which non-specifically stimulates a large population of T-lymphocytes. Their clonal proliferation often leads into a cytokine storm, which is responsible for the clinical manifestations. These diseases differ in their severity and in their clinical expression, ranging from exclusively cutaneous involvement to the presence of potentially lethal multi-organ dysfunction. In recent times, the presentation of these diseases has increased considerably, especially in the pediatric population, thanks to the contribution of the COVID-19 virus in its role as superantigen. We present 6 clinical cases in the pediatric population that presented symptoms attributable to disease due to superantigens.